Existence and Controllability Results for Nonlocal Fractional Impulsive Differential Inclusions in Banach Spaces - JinRong Wang; Ahmed G. Ibrahim (Journal of Function Spaces and Applications)
We firstly deal with the existence of mild solutions for nonlocal fractional impulsive semilinear differential inclusions involving Caputo derivative in Banach spaces in the case when the linear part is the infinitesimal generator of a semigroup not necessarily compact. Meanwhile, we prove the compactness property of the set of solutions. Secondly, we establish two cases of sufficient conditions for the controllability of the considered control problems.